Refined DNA repair manipulation enables a universal knock-in strategy in mouse embryos - Hongyu Chen; Qingtong Tan; Li Li; Lanxin Li; Jiqiang Fu; Wencheng Zhu; Jie Li; Yining Wang; Shiyan Li; Huimin Li; Yidi Sun; Qiang Sun; et al. (Nature Communications)
Abstract The design and screening of sgRNA in CRISPR-dependent gene knock-in is always laborious. Therefore, a universal and highly efficient knock-in strategy suitable for different sgRNA target sites is necessary. In our mouse embryo study, we find that the knock-in efficiency guided by adjacent sgRNAs varies greatly, although similar indel frequency. MMEJ-biased sgRNAs usually lead to high knock-in efficiency, whereas NHEJ-biased sgRNAs result in low knock-in efficiency. Blocking MMEJ repair by knocking down Polq can enhance knock-in efficiency, but inhibiting NHEJ repair shows variable effects. We identify a compound, AZD7648, that can shift DSBs repair towards MMEJ. Finally, by combining AZD7648 treatment with Polq knockdown, we develop a universal and highly efficient knock-in strategy in mouse embryos. This approach is validated at more than ten genomic loci, achieving up to 90% knock-in efficiency, marking a significant advancement toward predictable and highly efficient CRISPR-mediated gene integration.